Students’ Authentic Conversations with Tourists in a Banyuwangi PBL Project - Anwar, Saiful; Kumaini, Ruston (English Education: Jurnal Tadris Bahasa Inggris, 2025)
This study investigates how real-life conversations with international tourists enhance the speaking competence of English for Tour Guide students in Banyuwangi. The project was designed to provide authentic language develop both linguistic and intercultural competence. Qualitative descriptive as approach and data were collected through observations and students’ reflective reports. The findings indicate that while students displayed enthusiasm, hospitality, and the ability to initiate interactions, they faced significant challenges in vocabulary, pronunciation, and translating cultural concepts into meaningful English explanations. Literal translations often reduced the symbolic value of rituals such as Gandrung Sewu and Tumpengan, leading to incomplete communication. Psychological barriers, including nervousness and fear of making mistakes, also emerged, although these decreased once interactions began. Non-verbal strategies such as gestures and visual aids supported communication but required stronger verbal elaboration. Overall, the study suggests that authentic exposure provides powerful opportunities for building communicative confidence and resilience, yet students need structured preparation to succeed in unpredictable intercultural encounters. By combining linguistic, intercultural, and psychological readiness, students can perform more effectively as cultural mediators and ambassadors of Banyuwangi in global tourism contexts.